Hipertensi pada Lansia di Pondok Haji Muhammad Ridwan di Desa Rondaman Dolok - Sagala, Nanda Suryani; Napitupulu, Mastiur (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
In Indonesia, hypertension is still a big challenge. This is because hypertension is a condition that is often found in primary health care. About 1 in 3 Indonesians suffer from hypertension. Based on the prevalence, the percentage of hypertension sufferers who are over 18 years old is 25.8%. The number of hypertension cases diagnosed by health workers was only 36.8% and the rest (63.2%) were undiagnosed. After conducting health education about hypertension, clients are able to find out about hypertension. Pondok Haji Muhammad Ridwan, Rondaman Dolok Village is one of the elderly lodgings in North Padang Lawas Regency. From the survey conducted by the community service team with interviews with the management, it was found that more than 60 elderly people were present in this cottage every period and where the elderly were known to have hypertension that did not receive regular treatment. This service activity was held using the method of health checks for the elderly who live in the Haji Muhammad Ridwan lodge, Rondaman Dolok Village. The activity begins with registration, then a health check is carried out, namely blood pressure, height and weight. After doing blood pressure checks, it was found that there were 36 elderly people who suffered from hypertension, most of them had controlled blood pressure. However, this condition needs to be maintained and even improved so that those with hypertension can be controlled and prevent them from experiencing further complications.